Bahasa Indonesia dalam Komunikasi Bisnis: Studi Kasus UMKM di Gunung Anyar, Surabaya - Nisak, Marsada Khoirotun; Putri, Riska Amelia; Wijaya, Ratu Pasha Anayya; Pratiwi, Ika Lusiana; Ditya, Tabitha Putri; Anggraeni, Natalia Desy (TSAQOFAH, 2025)
This research examines the use of Indonesian in trade communication by small-scale Small and Medium Enterprises (MSMEs) in Gunung Anyar, Surabaya. The most central thing is how Indonesian is used in various communication perspectives, such as marketing, negotiations and customer interactions. The method used can be a case study with a qualitative approach through semi-structured interviews, coordinating perceptions and examining documentation. This research shows that MSMEs use Indonesian as an effective communication tool to reach wider advertising and build closeness with customers, especially in the local market. However, there are variations in dialect usage that are influenced by statistical variables, social segments, and trade. This research confirms the importance of Indonesian as a key component in building comprehensive and efficient trade communications. These findings provide suggestions for creating a trade communication methodology for MSMEs in the digital era.